Low-frequency 3D synthetic aperture radar for the remote intelligence of building interiors - Andre, Daniel; Faulkner, B.; Finnis, Mark V. (Cranfield University, 2017)
Low-frequency (LF) synthetic aperture radar (SAR) images offer a viable approach to determining the architecture and contents of buildings and underground bunkers via remote sensing. Often however, standard 2D SAR images can be difficult to interpret due to component signatures from different heights being projected into the scene leading to confused results. In this research, measurement results have shown that the full Nyquist 2D aperture scan approach to 3D through-wall LF SAR provides focussed 3D resolution of a wall and contents behind it in a number of frequency bands. Full-scale radar system upgrades are ongoing in order to investigate numerous other scenarios, however in the meantime, sparse 2D aperture scanning investigations have been undertaken with a prototype radar scanner. Whilst this kind of collection cannot achieve the low sidelobe levels of full Nyquist 2D aperture collections, these prototype scanner measurements are much faster to collect, and have shown encouraging results of sufficient image quality to determine the 3D configuration of prominent features in the target scene, albeit with higher sidelobe or image artefact levels.